2017
DOI: 10.2140/agt.2017.17.869
|View full text |Cite
|
Sign up to set email alerts
|

Infinite loop spaces and nilpotent K–theory

Abstract: Using a construction derived from the descending central series of the free groups, we produce filtrations by infinite loop spaces of the classical infinite loop spaces BSU , BU , BSO, BO, BSp, BGL ∞ (R) + and Q 0 (S 0 ). We show that these infinite loop spaces are the zero spaces of non-unital E ∞ -ring spectra. We introduce the notion of q-nilpotent K-theory of a CW-complex X for any q ≥ 2, which extends the notion of commutative K-theory defined by Adem-Gómez, and show that it is represented by Z × B(q, U )… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 21 publications
0
51
0
Order By: Relevance
“…Naturality of the isomorphisms {±I} × SO(2n + 1) ∼ = O(2n + 1) with respect to the aforementioned inclusions and the induced isomorphisms at the level of π 2 also give the claimed isomorphisms in part (3).…”
Section: 2mentioning
confidence: 84%
See 3 more Smart Citations
“…Naturality of the isomorphisms {±I} × SO(2n + 1) ∼ = O(2n + 1) with respect to the aforementioned inclusions and the induced isomorphisms at the level of π 2 also give the claimed isomorphisms in part (3).…”
Section: 2mentioning
confidence: 84%
“…Similar considerations with unitary matrices yield complex commutative K-theory. There is a natural forgetful map KO com (X) → KO 0 (X), and in Adem-Gómez-Lind-Tillman [3] it was shown that this map admits a splitting (additively), and the same holds in the complex case.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…A key property of BG is that it classifies principal G-bundles; there is a bijection between the set of isomorphism classes of principal G-bundles over a CW-complex X and the set of homotopy classes of maps X → BG. It is shown in [2] that B(q, G) is a classifying space for principal G-bundles of certain type, so called principal G-bundles of transitional nilpotency class less than q. It is a natural problem to study the homotopy type of B(q, G).…”
Section: Introductionmentioning
confidence: 99%